Hubungan Kadar C-Reactive Protein (CRP) Dengan Derajat Hipertensi Pada Pasien Di Rumah Sakit X Yogyakarta - Ratna Wulansari; Farida Noor Irfani; Siti Khotimah (Bajang Institute, 2026)
Hypertension is a major noncommunicable disease (NCD) worldwide and is closely associated with impaired vasodilation and endothelial dysfunction, which trigger vascular inflammation. The inflammatory process stimulates the release of inflammatory cytokines, one of which is C-reactive protein (CRP). Elevated CRP levels reflect systemic inflammation and cardiovascular complications. This study aims to determine the relationship between CRP levels and the severity of hypertension in patients at Hospital X in Yogyakarta. This study employed a quantitative analytical observational design with a retrospective longitudinal approach. The data used were secondary data from the medical records of hypertensive patients who underwent CRP testing. The sampling technique used total sampling based on inclusion and exclusion criteria, with a sample size of 39 patients. Data were analyzed using SPSS 20 through normality tests, descriptive analysis, and Spearman’s rank correlation test. The results showed that the majority of respondents were in early adulthood (26–35 years old), accounting for 25.6%, with an equal proportion of women and men-5 patients each. Most patients had normal systolic blood pressure (43.6%), normal diastolic blood pressure (64.1%), and normal CRP levels (61.5%). The results of the normality test indicated that the data were not normally distributed (p < 0.05). The results of the Spearman rank correlation test showed no significant correlation between systolic blood pressure and CRP levels (r = 0.083; p = 0.614) or between diastolic blood pressure and CRP levels (r = 0.069; p = 0.677). The conclusion of this study is that there is no significant association between CRP levels and the severity of hypertension in patients at Hospital X in Yogyakarta.